Health professionals' views and experiences around the dietary and lifestyle management of gestational diabetes in New Zealand. Issue 2 (6th February 2022) - North, Sylvia; Crofts, Catherine; Zinn, Caryn
Abstract: Aim: This study aimed to investigate New Zealand health professionals' views and experiences around the dietary and lifestyle management of gestational diabetes. Methods: Semi‐structured interviews were conducted remotely with health professionals; sessions were recorded and transcribed. Core themes were extracted using inductive thematic analysis using a framework method. Results: Twenty‐seven health professionals were interviewed (13 diabetes dietitians, 8 specialist diabetes midwives, 2 community midwives, 1 antenatal clinic midwife, 1 obstetrician and 2 endocrinologists). Themes were organised into three central domains: (a) Social and cultural barriers, (b) Service provision and (c) Nutrition advice. Enabling themes included professional collaboration, innovation and creating trusting and supportive environments. Key barriers identified included accessibility, cultural barriers, overwhelmed service, fragmentation and conflicting information and nutrition resource gaps. Conclusions: Findings highlight foremost a deficit in primary antenatal nutrition advice that may play a significant role in the fragmentation identified. Investment in community‐inclusive services providing antenatal nutrition and diabetes education appears critical to overcome barriers associated with misinformation and poor outcomes. Pathways to include nutrition education from various primary care health providers should be investigated to ease the burden from specialist gestational diabetes clinicians and allow effective delegation of dietetic resources. Revision of current nutrition guidelines for the management of gestational diabetes in New Zealand is needed to facilitate consistent messaging and standards of care.